Effects of enzymatic blood defibrination in subcortical arteriosclerotic encephalopathy. Issue 8 (August 1988) - Ringelstein, E B; Mauckner, A; Schneider, R; Sturm, W; Doering, W; Wolf, S; Maurin, N; Willmes, K; Schlenker, M; Brückmann, H
Abstract : Plasma hyperviscosity is a striking abnormality in patients suffering from subcortical arteriosclerotic encephalopathy (SAE) and is thought to perpetuate the chronic ischaemic demyelinating process of the periventricular white matter. Ancrod, a defibrinating enzyme, was given to 10 patients with SAE in an attempt to reduce plasma fibrinogen, which would thus normalise hyperviscosity. This was paralleled by a significant improvement of the initially abnormal retinal arteriovenous passage time, as well as a significant augmentation of the CO2-induced cerebral vasomotor response. This did not lead, however, to any clinical improvement with respect to performance of neuropsychological tests, recurrences of strokes during a 6 month observation period or improvement of various audiological parameters. The findings indicate that hyperviscosity in patients with SAE is merely an epiphenomenon. A potentially reversible, chronic penumbral state of the brain tissue apparently does not exist in SAE.